PENGARUH CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Thaddeus David Bintang Sihombing; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Good Corporate Governance on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Profitability is measured using Good Corporate Governance (ROA). CSR is measured by the Corporate Social Responsibility Disclosure Index (CSRDI) based on GRI standards, GCG is proxied by independent commissioners, institutional ownership, and audit committees, while Good Corporate Governance is measured using the PROPER rating. This quantitative study uses multiple linear Regression with Agency of manufacturing companies that publish Annual reports, Sustainability reports, and PROPER ratings. Secondary data are obtained from company reports, the IDX, and the Ministry of Environment and Forestry. The results provide empirical evidence on the role of CSR, GCG, and Good Corporate Governance in improving corporate profitability and contribute to accounting and sustainability literature, as well as to managerial and policy decision making.